The Influence Of Leadership, Organizational Culture, And Work Competence On Employee Performance Through Work Motivation - Tito Widayanto; Sukmo Hadi Nugroho (LPPM Universitas Trunojoyo Madura, 2022)
This research was conducted to explore the influence of leadership, organizational culture, and work competence on employee performance which is mediated by work motivation. This research is a development of previous research on employees in one of the local government agencies. The contribution of this research is expected to be able to provide new information at the theoretical/scientific level of human resource management and add new references and managerial implications that can be positively applied to non-profit organizations. Referring to the results of previous research and empirical theory related to the learning process of human resource management, this research was conducted using a survey data collection method by distributing questionnaires online, respondents were selected based on a purposive method sampling of ministry employees in charge of coordination in the fields of politics, law, and security. The analysis in this study uses factor analysis and Lisrel structural equation modeling (SEM). The findings from this study are that leadership and organizational culture are not directly related to employee performance, but the role of leadership and organizational culture can be related to employee performance through the mediation of work motivation. The managerial implication of this research for the organization is being able to encourage the role of a leader to be able to improve the performance of its employees in the organization and the various cultures within the organization can be uniformed following the culture which can provide positive changes to the work motivation of employees to achieve organizational goals.